The Effect of a 12-Week Plyometric and Tabata Training Program with Three Weekly Sessions on Cardiovascular Efficiency in Elite Soccer Players - Narayanan, Nidhin Muthrathiparambil; Sundar, Kayambu; Salvi, Nirmal Michael; Yashpal; Karmakar, Debajit; Saha, Sohom; Orhan, Bekir Erhan; Boby, Farjana Akter; Astuti, Yuni (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to examine the effects of a 12-week plyometric training program and a Tabata regimen on cardiovascular efficiency in elite soccer players. Materials and methods. Sixty male inter-university players, aged 20.79 ± 1.75 years, were randomly assigned to the Plyometric Training Group (PTG, n = 20), Tabata Training Group (TTG, n = 20), or Control Group (CG, n = 20). Cardiovascular metrics, including vital capacity, resting heart rate, mean arterial blood pressure, breath-holding time, and respiratory rate, were assessed before and after the program. Both PTG and TTG completed three 90-minute sessions on a weekly basis. Results. The results revealed that both the PTG and TTG showed significant improvements in cardiovascular efficiency. Vital capacity increased by 30.83% (d = 1.24, p < 0.001) in PTG and by 34.61% (d = 1.52, p < 0.001) in TTG. Resting heart rate decreased by 12.36% (d = 1.74, p < 0.001) in PTG and by 15.18% (d = 1.82, p < 0.001) in TTG. Breath-holding time increased by 29.86% (d = 2.12, p < 0.001) in PTG and by 34.42% (d = 2.35, p < 0.001) in TTG. Respiratory rate decreased by 28.07% (d = 1.04, p < 0.001) in PTG and by 28.33% (d = 1.10, p < 0.001) in TTG. These findings highlight the substantial positive impact of both training methods on cardiovascular efficiency in elite soccer players. Conclusions. In conclusion, the implementation of a plyometric and Tabata training program has been found to produce significant improvements in cardiovascular efficiency in elite soccer players, making them valuable preseason conditioning strategies to enhance endurance, performance, and overall athletic abilities.